Trunk strength and function using the multidirectional reach distance in individuals with non-traumatic spinal cord injury. (September 2014) - Gabison, Sharon; Verrier, Molly C.; Nadeau, Sylvie; Gagnon, Dany H.; Roy, Audrey; Flett, Heather M.
Abstract : Context: Trunk control is essential to engage in activities of daily living. Measuring trunk strength and function in persons with spinal cord injury (SCI) is difficult. Trunk function has not been studied in non-traumatic SCI (NTSCI). Objectives: To characterize changes in trunk strength and seated functional reach in individuals with NTSCI during inpatient rehabilitation. To determine if trunk strength and seated reach differ between walkers and wheelchair users. To explore relationships between trunk and hip strength and seated functional reach. Design: Observational study. Setting: Two SCI rehabilitation facilities. Participants: 32 subacute inpatients (mean age 48.0 ± 15.4 years). Outcome measures: Isometric strength of trunk and hip and function (Multidirectional Reach Test: MDRT) were assessed at admission and within 2 weeks of discharge. Analysis of variance was conducted for admission measures (MDRT, hip and trunk strength) between walkers and wheelchair users. Changes in MDRT, hip and trunk strength were evaluated using parametric and non-parametric statistics. The level of association between changes in values of MRDT and strength was also examined. Results: Significant differences between walkers and wheelchair users were found for strength measures ( P  < 0.05) but not for MDRT. Left- and right-sided reaches increased in wheelchair users only ( P  < 0.05). Associations between changes in hip strength, trunk strength, and reach distance were found ( R  = 0.67–0.73). Conclusion: In clinical settings, it is feasible and relevant to assess trunk, hip strength, and MRDT. Future studies require strategies to increase the number of participants assessed, in order to inform clinicians about relevant rehabilitation interventions.